Visualisasi Dan Perbandingan Efisiensi Algoritma A*, Greedy, Dan Dijkstra Dalam Mencari Rute Terpendek Di Kota Medan Menggunakan Openstreetmap - Alvito, Paris; Ikhsan, Muhammad (JURNAL RISET KOMPUTER (JURIKOM), 2025)
This study compares the efficiency of A*, Greedy, and Dijkstra algorithms in finding the shortest path on the road network of Medan City using geospatial data from OpenStreetMap. An interactive visualization system was developed using web-based technologies such as React.js, MapLibre GL, and Deck.gl to display the pathfinding process in real-time. The evaluation was conducted on two graph scales using six parameters: execution time, number of explored nodes, path length, memory usage, number of nodes in the path, and scalability. The results show that the A* algorithm is the most efficient overall, achieving 0.13 seconds with 17 nodes explored on the small graph, and 0.29 seconds with 52 nodes on the large graph. Dijkstra yields the most accurate paths but with significantly more node exploration and memory consumption, while Greedy is the fastest (0.11 seconds) but less accurate. This research contributes to the understanding of pathfinding algorithms and their implementation in map-based systems.